Enhancing electrical conductivity of coal-derived graphite by boric acid catalysis: Correlating 2H/3R phase ratio with crystallite structure - Xiaomei Zhang; Xinyu Chen; Yeersheng Jiangbaolati; Shanshan Liu; Jidun Sha; Xiaoming Zhang; Hao Chen; Shuo Feng (PLoS ONE, 2026)
Natural graphite scarcity and conventional catalyst-induced defects limit the scalable production of high-performance coal-derived graphite. Herein, we demonstrate boric acid (H 3 BO 3 ) as a green catalyst for coal graphitization by comparing with Fe 2 (SO 4 ) 3 , FeCl 3 , FeS 2 , and H 3 BO 3 +FeCl 3 , with a focus on crystallite structure, 2H/3R polytypic graphite, and electrical conductivity. X-ray diffraction (XRD) analysis reveals that H 3 BO 3 catalysis significantly elevates structural order, presenting a narrow and sharp (002) band, and increasing in-plane crystallite size (La), stacking height (Lc), and the proportion of graphite (f ɑ ) in the bulk sample. High resolution transmission electron microscopy (HR TEM) identifies graphite-like nanostructures and planar graphene nanostructure as the key contributor to electrical conductivity. A linear relationship between La and 2H/3R is established, associated with electrical conductivity, confirming the intrinsic correlation between graphite-like nanostructures and crystalline size. This work clarifies the feasibility of boric acid, providing a low-cost and efficient strategy for fabricating high-performance coal-derived graphite, which holds great potential for applications in energy storage and conductive fields.